Perbandingan Kinerja Keuangan: Sebuah Analisis Sistem Konvensioanal dan Syari’ah - Ragil Puspita Wulan Aprilia, Putri; Setiono, Hari; Fitri Isnaini, Nurdiana (PRIVE: Jurnal Riset Akuntansi dan Keuangan, 2024)
Bank performance is an element that needs to be monitored in banking activities. The capacity of one company to run and distribute its resources will show a bank's performance, so that each bank will have good performance in order to survive among the increasingly selective banking industry. The purpose of this study is to see the differences in the financial performance of conventional BRI and BRI Syariah banks. This research is classified as quantitative research and secondary data sources. Purposive sampling technique was used to take samples. The object of this research is Conventional BRI and BRI Syariah which have published annual financial reports or annual reports for the 2016-2020 period. The analytical method applied is the independent sample T test and the Mann Witney U test. The results of the CAR test have no significant difference between Conventional BRI and Sharia BRI. Meanwhile, the results of the NPL, ROA, LDR, BOPO, ROE and PR tests showed significant differences between Conventional BRI and Sharia BRI. The conclusion is that conventional BRI Bank's financial ratios are better than Sharia BRI's Bank. From the aspect of quality, profitability, liquidity and solvency, Conventional BRI Bank is better than Sharia BRI Bank. However, in terms of capital, BRI Syariah Bank is better than Conventional BRI Bank.